Spiral antennas for the generation of bessel beams with tunable nondiffractive range. (17th May 2021) - Benedetti, Alessio; Fuscaldo, Walter; Comite, Davide; Tofani, Silvia; Baccarelli, Paolo; Galli, Alessandro; Burghignoli, Paolo
Abstract: Backward cylindrical leaky waves radiating in the direction of their central axis represent an efficient solution for generating nondiffracting Bessel-like beams. The structures proposed so far to support such waves, constituted by concentric metal rings printed on a grounded dielectric slab, ensure the formation of nondiffractive field patterns with preset unchangeable configurations at a given frequency. Here, we propose the adoption of subwavelength spiral filaments with controlled patterning of the envelope figure by dynamic mechanical deformations, in order to achieve spatial tuning of the nondiffractive region in its size and shape. Precise guidelines and examples are provided to describe the proposed design technique and underline the inherent advantages of this alternative technological solution.